Are Emerging Asia's Reserves Really Too High? - Ruiz-Arranz, Marta; Zavadjil, Milan (Washington, D.C. : International Monetary Fund, 2008)
Empirical analysis does not suggest that reserves are "too high" in the majority of Asian countries, though China may be a special case. Much of the reserve increase in Asia can be explained by an optimal insurance model under which reserves provide a steady source of liquidity to cushion the impact of a sudden stop in capital inflows on output and consumption. Moreover, the benefits of reserves in terms of reduced spreads on privately held external debt further explains the observed growth in reserves since 1997-98. Using threshold estimation techniques, the paper shows that most of Asia can still benefit from higher reserves in terms of reduced borrowing costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet